The Last Embassy : The Dutch Mission of 1795 and the Forgotten History of Western Encounters with China - Andrade, Tonio (Book collections on Project MUSE., 2021)
"In the typical narrative of modern Sino-European relations, George Macartney's disastrous 1793 mission to China plays a central role. His failure to open China to trade and diplomatic relations with Britain sets the stage for a long and bitter clash of cultures that led to the Opium Wars of the nineteenth century and perhaps even to the mistrust that still pervades relations today. In this book, Tonio Andrade draws on a wealth of neglected archival material to tell a very different story: that of the last European delegation that was ever received in the traditional Chinese court, the Dutch mission of 1794-95"--